Evaluation Managed Care Policy, Fraud Prevention and Commitment-Based Capitation in the Era of National Health Insurance in Bengkulu Province Used Realist Evaluation - Susilo Wulan (Jurnal Kebijakan Kesehatan Indonesia, 2021)
Regulations related to health service quality policies in the era of National Health Insurance are needed to evaluate the effectiveness of programs based on sufficient evidence to become local as well as national policies. This research is important to do to support Universal Health Coverage (UHC) as issued by WHO. This study aims to evaluate the implementation of health service quality policy regulations and identify mechanisms of change and contextual factors that affect the implementation of regulations. Evaluation is carried out using a realist evaluation approach and analyzed in the form of a context, mechanism, and outcome configuration. The research was conducted in Bengkulu Province in 2018-2019 with the research subjects consisting of the director of the hospital, TKMKB, the fraud prevention team, the Health Office and the head of the Puskesmas. The sample selection used purposive sampling and data collection was carried out through in-depth interviews. Quality control and cost control (KMKB) programs, fraud prevention and Commitment-Based Capitation (KBK) are running in Bengkulu province. KMKB operates because of the SK which is always updated by BPJS Kesehatan every year, support from BPJS Kesehatan in the form of operational facilitation, coordination and incentives. The anti-fraud team in Bengkulu province in general has been formed at the district / city health office and hospital level, but not yet at the provincial level, this is because there is another team that has similar duties to the anti-fraud team at the provincial health office while at the health office district / city they are aware of the importance of the anti-fraud team. The KBK program shows that in general the target indicator for non-specialist referrals in Bengkulu province is achieved, namely 5%, but there are also city districts that have not been achieved, this is achieved because the Puskesmas has doctors in Bengkulu province, the competence of doctors is sufficient, adequate facilities and infrastructure, staff to receive capitation fund incentives, there is a JKN Monev team that is always active in conducting socialization, monitoring and evaluation at all Puskesmas, especially those that do not reach the target non-specialized referral indicator This study provides an overview of aspects of the context, mechanisms and outputs of health service quality policy regulations in the JKN era.